2019
DOI: 10.3390/ijms20246304
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Molecular Imprinting and the Evolution of MIP Nanoparticles as Plastic Antibodies—Synthesis and Applications

Abstract: Materials that can mimic the molecular recognition-based functions found in biology are a significant goal for science and technology. Molecular imprinting is a technology that addresses this challenge by providing polymeric materials with antibody-like recognition characteristics. Recently, significant progress has been achieved in solving many of the practical problems traditionally associated with molecularly imprinted polymers (MIPs), such as difficulties with imprinting of proteins, poor compatibility wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 174 publications
0
93
0
Order By: Relevance
“…38 Moreover, the graing of MIPs shells onto UCNPs cores is easy to form aggregation, resulting in poor penetration of light through the dense suspension. 39 Our study demonstrated that the synthesized UCNPs can incorporated with MIPs be employed as uorescence probes for the rapid detection of molecules. However, the sensitivity and selectivity need further verify.…”
Section: Equilibrium Bindingmentioning
confidence: 71%
“…38 Moreover, the graing of MIPs shells onto UCNPs cores is easy to form aggregation, resulting in poor penetration of light through the dense suspension. 39 Our study demonstrated that the synthesized UCNPs can incorporated with MIPs be employed as uorescence probes for the rapid detection of molecules. However, the sensitivity and selectivity need further verify.…”
Section: Equilibrium Bindingmentioning
confidence: 71%
“…However molecular imprinting of proteins is not very trivial and is related to several critical challenges [ 184 ] such as extraction of proteins from MIP-matrix and multiple reusability of such imprinted protein-based sensors ( Figure 6 ) [ 2 , 185 ], conformational changes of proteins during imprinting phase [ 186 ], and suitable orientation of proteins during the imprinting phase [ 187 ]. Hence, due to numerous efforts of various research groups, significant progress has been achieved in the development of MIP-based sensors for the determination of proteins, which sometimes are called as “plastic antibodies” [ 188 , 189 ], “artificial receptors” or “synthetic receptors” [ 2 , 185 , 190 ]. During this development many practical problems traditionally associated with molecularly imprinted polymers (MIPs), should be solved, that includes some challenges related to imprinting of proteins, namely, hydrophobic nature of some polymers that are applied for the formation of MIPs, insufficient compatibility with template, and the formation of not-specific binding regions in imprinted polymers that are responsible for non-specific binding of different proteins and/or other molecules.…”
Section: Formation Of Mips Imprinted By Proteins and By Other Largmentioning
confidence: 99%
“…PI methods include emulsion polymerization, suspension polymerization, precipitation polymerization, and seed polymerization. These methods have already been extensively reviewed elsewhere [ 19 , 37 , 50 , 51 ], and their main advantages and disadvantages are briefly summarized in Table 1 . The main differences to classic BI are (i) the presence of surfactants/stabilizers, and (ii) the much lower monomer and template concentration in the pre-polymer solution [ 10 ].…”
Section: Fabrication Strategies For Mipsmentioning
confidence: 99%